Los Padres antes que los griegos. La carne y la elaboración del enfoque foucaultiano de la subjetividad - Colombo, Agustín (2025)
Michel Foucault’s late account of subjectivity has been mainly studied through Foucault’s investigation on ancient philosophy. Such interpretative tendency has undoubtedly been influenced by the publication of volumes II and III of History of Sexuality, which took place in the same year of Foucault’s death. Forty years after that event, this article investigates the impact that Foucault’s posthumous publication on Christianity has, in particular History of Sexuality vol. 4, Confessions of the Flesh, on the understanding of the development of Foucault’s account of subjectivity. In doing so, this article aims to show, against the conventional interpretation, that Foucault coins his late approach to subjectivity in the context of his research on the Church Fathers, before turning his attention to ancient philosophy.